Perancangan Dan Pembuatan Alat Penukar Kalor Desorber Jenis Finned Tube Pada Sistem Adsorpsi Double Bed Adsorber Dengan Silika Gel-Air Sebagai Pasangan Adsorben-Adsorbat - Aldi Ansyah Kurniawan Lubis; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The issue of global warming and the amount of energy consumption is one of the biggest problems of the air conditioning system and refrigeration used today, so technology that isenvironmentally friendly and also energy efficient is needed. The adsorption cooling system is one ofthe technologies for air conditioning and refrigeration systems that are energy efficient and environmentally friendly because the refrigerants used do not contain haolocarbon and not usingcompressors in the system so that it saves energy. In this study a double bed adsorber adsorption system with silica gel-water is designed as an adsorbent-adsorbate. as an adsorbent-adsorbate. The adsorption cooling system contains 2 adsorber and finned and tube pieces as heat exchangers. Where the fin uses 1 mm thick alumanium and the tube uses copper outer diameter of 9.52 mm with a time ofadsorption and desorption for 20 minutes.Keywords : Adsorption, Design, Adsorben, Adsorbat.